2009
DOI: 10.1124/dmd.109.030429
|View full text |Cite
|
Sign up to set email alerts
|

Current Cytochrome P450 Phenotyping Methods Applied to Metabolic Drug-Drug Interaction Prediction in Dogs

Abstract: ABSTRACT:Recombinant cytochrome P450 (P450) phenotyping, different approaches for estimating fraction metabolized (f m ), and multiple measures of in vivo inhibitor exposure were tested for their ability to predict drug interaction magnitude in dogs. In previous reports, midazolam-ketoconazole interaction studies in dogs have been attributed to inhibition of CYP3A pathways. However, in vitro phenotyping studies demonstrated higher apparent intrinsic clearances (CL int,app ) of midazolam with canine CYP2B11 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…We found that the experimental animals had high oral BAs and low CL int values of caffeine, similar to those of humans. A significant first-pass effect was not detected after the oral administration of caffeine and its levels in the microsomes of humans and some experimental animals decreased slowly [30,[42][43][44][45]. Furthermore, the AUC 0-24h ratios of paraxanthine/caffeine in the 5 experimental animals were within ± 3-fold that in humans [33].…”
Section: Discussionmentioning
confidence: 72%
“…We found that the experimental animals had high oral BAs and low CL int values of caffeine, similar to those of humans. A significant first-pass effect was not detected after the oral administration of caffeine and its levels in the microsomes of humans and some experimental animals decreased slowly [30,[42][43][44][45]. Furthermore, the AUC 0-24h ratios of paraxanthine/caffeine in the 5 experimental animals were within ± 3-fold that in humans [33].…”
Section: Discussionmentioning
confidence: 72%
“…However significant species differences exist. For example midazolam is metabolized exclusively by human CYP3A4 and CYP3A5 (but not by human CYP2B6) while dog CYP2B11 (and not CYP3A12) primarily metabolizes midazolam 6 . Similarly, both dog CYP1A2 and dog CYP2A13 metabolize phenacetin 7, 8 , while only human CYP1A2 (and not human CYP2A6) metabolizes this drug.…”
Section: Dog-human Cyp Similarities and Differencesmentioning
confidence: 99%
“…The reported studies in dogs mainly focus on the expression and catalytic activity of metabolic enzymes in the liver (Kyokawa et al, 2001;Mills et al, 2010). Less is known about the intestinal expression distribution of cytochromes P450 (P450s), UDP-glucuronosyltransferases (UGTs) (Bock et al, 2002;Mealey et al, 2008), and transporters (Conrad et al, 2001) or about P450 substrate specificity (Fraser et al, 1997;Turpeinen et al, 2007;Locuson et al, 2009) and intersubject variability in expression.…”
Section: Introductionmentioning
confidence: 99%